Thermal and Morphological Characterization of Coagulation-Processed Nanocomposite of Polypropylene and Bio-nanocarbon obtained from Bamboo - Nisa, Z.U. (Institute of Electrical and Electronics Engineers Inc., 2021)
Bio nano carbon obtained from bamboo (Gigantochloa scortechinii) was used as filler in polypropylene to synthesize its nanocomposite using the coagulation technique. The nanocomposite was prepared with two percent filler loading. Structural elucidation of the nanocomposite was carried out by Fourier transform infrared spectroscopy, the morphological study was done by Field emission Scanning electron and Thermal studies were investigated using Thermogravimetric Analysis and Differential Scanning Calorimetry techniques. The obtained results are interrelated to the neat polypropylene. Â© 2021 IEEE.